Japan's liquidity trap - Tanweer Akram (Levy Economics Institute of Bard College, 2016)
Japan has experienced stagnation, deflation, and low interest rates for decades. It is caught in a liquidity trap. This paper examines Japan's liquidity trap in light of the structure and performance of the country's economy since the onset of stagnation. It also analyzes the country's liquidity trap in terms of the different strands in the theoretical literature. It is argued that insights from a Keynesian perspective are still quite relevant. The Keynesian perspective is useful not just for understanding Japan's liquidity trap but also for formulating and implementing policies that can overcome the liquidity trap and foster renewed economic growth and prosperity. Paul Krugman (1998a, b) and Ben Bernanke (2000; 2002) identify low inflation and deflation risks as the cause of a liquidity trap. Hence, they advocate a credible commitment by the central bank to sustained monetary easing as the key to reigniting inflation, creating an exit from a liquidity trap through low interest rates and quantitative easing. In contrast, for John Maynard Keynes (2007 [1936]) the possibility of a liquidity trap arises from a sharp rise in investors' liquidity preference and the fear of capital losses due to uncertainty about the direction of interest rates. His analysis calls for an integrated strategy for overcoming a liquidity trap. This strategy consists of vigorous fiscal policy and employment creation to induce a higher expected marginal efficiency of capital, while the central bank stabilizes the yield curve and reduces interest rate volatility to mitigate investors' expectations of capital loss. In light of Japan's experience, Keynes's analysis and proposal for generating effective demand might well be a more appropriate remedy for the country's liquidity trap.
Keywords: E02; E40; E43; E50; E52; E58; E60; 330; Liquidity Trap; Japan; Monetary Policy; Interest Rates